100 m World record could go as low as 9.48 s - Phillips, K. (The Journal of Experimental Biology, 2008)
2008 was a great summer for sports' fans. World records tumbled at the Beijing Olympics. Usain Bolt shattered both the 100 m and 200 m world records, knocking tenths of a second off each. People have been getting faster and faster over the last few decades, which made marathon runner Mark Denny, from Stanford University, wonder whether last century's massive increase in population could account for these dramatic improvements. He also wondered whether there are absolute limits on running speeds and, if so, how close are we to them? Suspecting that there are, Denny decided to scrutinise the running performances of humans and two other famous racing species, dogs and thoroughbred horses, to find how close modern runners are to their species' peak performances (p. 3836).